Need-based fertilizer nitrogen management using leaf colour chart in hybrid rice (Oryza sativa) - GUPTA, R K; SINGH, VARINDERPAL; SINGH, YADVINDER; SINGH, BIJAY; THIND, H S; KUMAR, AJAY; VASHISTHA, MONIKA (The Indian Journal of Agricultural Sciences, 2026)
Field experiments were conducted during 2006–08 to study the response of hybrid rice cultivar PHB 71 to fertilizer N and to study the possibility of improving N-use efficiency by affecting fertilizer N as per need of the crop as guided by leaf colour chart (LCC). Treatments included six rates of N application (0, 60, 90, 120,150 and 180 kg/ha) applied in three equal splits at fixed growth stages. The two need-based N management treatments comprised of application of 20 kg N / ha as basal dose and application of 30 kg N /ha whenever greenness first fully opened leaf from the top was less than shade 4 or 5 on the LCC. Hybrid rice PHB 71 showed significant response to application of N up to 120 kg N /ha applied in three equal split doses. Beyond this level fertilizer N-use efficiency was significantly reduced. The LCC shade 4 proved better than LCC shade 5 for guiding real time N management and achieving higher N-use efficiency. Application of 80–110 kg N /ha using threshold LCC shade 4 inclusive of 20 kg N /ha as basal dose produced grain yield of rice which was at par with the application of 120 kg N /ha applied in three equal split doses.